2009
DOI: 10.1116/1.3085723
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and surface electronic properties of ZnO single crystals and nanorods

Abstract: The surface chemistry of ZnO single crystals of (0001) and (101¯0) orientations and ZnO nanorods was studied using x-ray and ultraviolet photoelectron spectroscopies. Air drying and UV-ozone preparations were studied in particular as chemical treatments that could be applied to poly(3-hexylthiophene) (P3HT)-ZnO solar cells to enhance performance. The UV-ozone treatment showed negligible effect by photoelectron spectroscopy on the ZnO single crystal surfaces, but brought about electronic shifts consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…ZnO band alignment based on the ionization potential. The horizontal lines represent the experimental reported values: 7.82 eV for I b and 3.44 eV for the bulk band gap; , for the (101̅0) and (112̅0) a I s value of 8.00 eV , and 7.82 eV, respectively. “(D)” has the same meaning as in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ZnO band alignment based on the ionization potential. The horizontal lines represent the experimental reported values: 7.82 eV for I b and 3.44 eV for the bulk band gap; , for the (101̅0) and (112̅0) a I s value of 8.00 eV , and 7.82 eV, respectively. “(D)” has the same meaning as in Table .…”
Section: Resultsmentioning
confidence: 99%
“…This property is defined as the energy needed to take an electron from the Fermi level, which like I s , is very sensitive to the sample history, surface preparation procedure, the method of measurement and the facet involved. , For example, for the (101̅0) face, different work function values have been reported by experiment and theory: ca. 4.6 eV, ,,, ca. 4.3 eV. ,, Kuo et al reported a work function value of 3.74, 3.95, and 4.21 eV for as-deposited ZnO films, after Ar sputter cleaning and after exposure to oxygen plasma .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an n-type semiconductor with a direct wide bandgap of 3.3 eV [40]. The electronic properties have been widely studied for CuO and ZnO nanostructures [41][42][43]. By fabricating smoother surfaces with minimum defects of metal oxide dielectrics can utilize their good electrical insulation without compensating its high k [44].…”
Section: Electronic and Optical Properties Of Transition Metal Oxidesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] HPV devices promise advantages of both organic and inorganic materials. Organic materials offer high light absorption coefficients, flexibility, ease of processing, and structural diversity.…”
Section: Introductionmentioning
confidence: 99%